The interrater reliability of a routine outcome measure for infants and pre-schoolers aged under 48 months: Health of the Nation Outcome Scales for Infants. Issue 3 (22nd April 2021) - Brann, Peter; Culjak, Gordana; Kowalenko, Nick; Dickson, Rosemary; Coombs, Tim; Sved Williams, Anne; Hoehn, Elisabeth; Davies, Simon; Hoyland, Margaret; Burgess, Philip
Abstract : Background: A review of Australian mental health services identified a gap in routine outcome measures addressing social, emotional and behavioural domains for pre-schoolers and infants. The Child and Adolescent Mental Health Information Development Expert Advisory Panel Working Group developed the Health of the Nation Outcome Scales for Infants (HoNOSI), a clinician-reported routine outcome measure for use with those aged under 4 years. Prior psychometric testing showed that the HoNOSI was considered to show face validity, and that it met the standards for concurrent validity and internal consistency. Aims: We aimed to investigate the interrater reliability of the HoNOSI. Method: Forty-five infant mental health clinicians completed HoNOSI ratings on a set of five case vignettes. Results: Quadratic weighted kappa interrater reliability estimates showed the HoNOSI to have Almost Perfect interrater reliability for the HoNOSI total score. Of the 15 scales, one had Moderate, seven had Substantial and seven had Almost Perfect interrater reliability. Ten of the fifteen scales and the total score exceeded the COnsensus-based Standards for the Selection of Health Measurement INstruments criteria for interrater reliability ( κw ≥ 0.7). Conclusions: There has been a clear need for a routine outcome measure for use with infants and pre-schoolers. This study provides evidence of interrater reliability. The current findings, combined with the face and concurrent validity studies, support further examination of HoNOSI in real-world settings.